2011
DOI: 10.1128/iai.00019-11
|View full text |Cite
|
Sign up to set email alerts
|

PrsW Is Required for Colonization, Resistance to Antimicrobial Peptides, and Expression of Extracytoplasmic Function σ Factors in Clostridium difficile

Abstract: Clostridium difficile is an anaerobic, Gram-positive, spore-forming, opportunistic pathogen that is the most common cause of hospital-acquired infectious diarrhea. In numerous pathogens, stress response mechanisms are required for survival within the host. Extracytoplasmic function (ECF) factors are a major family of signal transduction systems, which sense and respond to extracellular stresses. We have identified three C. difficile ECF factors. These ECF factors, CsfT, CsfU, and CsfV, induce their own express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 62 publications
2
98
0
Order By: Relevance
“…OatA provides lysozyme resistance in pathogenic Staphylococcus species (5, 7) and Lactococcus lactis (62). Furthermore, possible orthologs of V were found to be induced by lysozyme exposure in Enterococcus faecalis (42) and Clostridium difficile (35). Together, these results suggest that B. subtilis sigV, and therefore the V regulon, might be induced by lysozyme and thereby provide lysozyme resistance.…”
Section: Induction Ofmentioning
confidence: 55%
“…OatA provides lysozyme resistance in pathogenic Staphylococcus species (5, 7) and Lactococcus lactis (62). Furthermore, possible orthologs of V were found to be induced by lysozyme exposure in Enterococcus faecalis (42) and Clostridium difficile (35). Together, these results suggest that B. subtilis sigV, and therefore the V regulon, might be induced by lysozyme and thereby provide lysozyme resistance.…”
Section: Induction Ofmentioning
confidence: 55%
“…This was not an obvious finding: cationic AMPs share a mechanism of action, and C. difficile has evolved numerous strategies to evade their attack (28). C. difficile has been described to be resistant to bacterially derived AMPs, like bacitracin, nisin, gallidermin, vancomycin, and polymyxin B, but also to host-derived AMPs, like lysozyme (46,50). Furthermore, resistance to mammalian SMAP-29 and LL-37 was reported for epidemic-associated PCR ribotype 027 isolates (33).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of surviving bacteria was calculated as 100 ϫ (1 Ϫ r/c), where c is the number of CFU in untreated controls (SB6 medium alone) and r is the number of CFU in treated samples. The concentration of defensin that caused 50% bacterial growth inhibition (IC 50 ) was calculated from a plot of percent inhibition versus the logarithm of defensin concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Homologs of the V system have been identified in Enterococcus faecalis and Clostridium difficile, where they are also induced in response to lysozyme (34)(35)(36). In E. faecalis, it has been demonstrated that V is required for resistance to lysozyme and is important for virulence in mouse models of systemic and urinary tract infection (35).…”
mentioning
confidence: 99%